2018
DOI: 10.1093/annonc/mdy438.006
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of controlled-release oxycodone for reducing pain due to oral mucositis in nasopharyngeal carcinoma patients treated with concurrent chemoradiotherapy: A prospective clinical trial

Abstract: Methods: A retrospective multicenter chart review of 604 patients with NPC who underwent CCRT from May 2005 to November 2014 was conducted (265 in the PEG group, and 339 in the non-PEG group). Baseline characteristics, weight loss outcome and treatment tolerance were examined and compared between the two groups. Risk factors of more than 10% weight loss during CCRT were assessed by multivariate analysis. Results: We found significantly more T3-T4 tumors (P ¼ 0.03), cisplatin-based regimen (P ¼ 0.01), and less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This study enrolled 56 NPC patients who received CCRT between 19th May 2015 and 23rd January 2018 at Sun Yat-sen University Cancer Center, Guangzhou, China, as part of a prospective clinical trial. The details of this trial have been described by Hua et al (13). In brief, all patients received triweekly cisplatin (100 mg/m 2 )-based CCRT concurrently with IMRT following the guidelines of our institute (15), and reported moderate or severe pain, as indicated by numerical rating scale [NRS] pain scores of 4-10.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…This study enrolled 56 NPC patients who received CCRT between 19th May 2015 and 23rd January 2018 at Sun Yat-sen University Cancer Center, Guangzhou, China, as part of a prospective clinical trial. The details of this trial have been described by Hua et al (13). In brief, all patients received triweekly cisplatin (100 mg/m 2 )-based CCRT concurrently with IMRT following the guidelines of our institute (15), and reported moderate or severe pain, as indicated by numerical rating scale [NRS] pain scores of 4-10.…”
Section: Study Populationmentioning
confidence: 99%
“…While many researchers have investigated the effects of sarcopenia on prognosis in head and neck cancers, the association with patientreported QOL remains unclear (8,(10)(11)(12). Our previous study found that QOL can affect patient response to treatment, as well as long-term survival (13,14). Importantly, the deterioration in QOL caused by sarcopenia often appears gradually, as the cumulative dose of radio-and chemotherapy increases.…”
Section: Introductionmentioning
confidence: 99%
“…Extra toxicity can also lead to a poor quality of life. 8 Therefore, identifying the patient or tumor characteristics associated with toxicity and survival can potentially help personalize treatment regimens and improve the quality of care in patients with NPC.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in our study, pain is the largest worsening symptom in NPC patients during the CCRT period, with the percentage of those experiencing severe pain sharply increasing from 2.8% at the beginning to 32.9% at the end of CCRT. Oral mucositis, which was highly prevalent among NPC patients who received radiotherapy, might be the major source of pain ( 38 ). Pain could substantially and adversely affect patients' quality of life, adherence to therapy, treatment efficacy, and satisfaction with care, and might be a clinically indicator of tumor progression ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%